Effectiveness of Biosaka and NPK Fertilizer Against Growth and Yield of Cucumber Plants in Red Yellow Podzolic Soil - Suryanti, Widya Aini; Ramadhan, Tris Haris; Supriyanto, Supriyanto (Perkebunan dan Lahan Tropika, 2024)
Cucumber plants are a popular fruit vegetable in Indonesia. The development of cucumber cultivation on PMK land has problems including poor macro and micro nutrients, mass pH and slow decomposition. Efforts are being made to overcome this problem by using NPK fertilizer to add macro and micro nutrients to the soil, as well as providing Biosaka to reduce excessive use of chemical fertilizers. Biosaka is an elicitor that functions to increase resistance to disease and pests. This research was conducted in Pontianak City, West Kalimantan. Taking place from May 2024 to June 2024. This research used a Split Plot Design consisting of 2 treatment factors repeated 3 times, each replication consisting of 4 sample plants. The first factor of giving Biosaka (F) consists of 2 levels, namely f1 = not given biosaka, f2 = given biosaka and giving NPK (N) consists of 4 levels, namely n1 = 0 g/polybag, n2 = 5 g/polybag, n3 = 10 g/polybag, n4 = 15 gpolybag. The observation variables observed were plant dry weight, root volume, number of fruit/plant, fruit diameter, fruit length, fruit/fruit weight and fruit/plant weight. The results of the research showed that giving 15 g NPK fertilizer/polybag was the best treatment for the growth of cucumber plants and giving 10 g NPK fertilizer/polybag was the best treatment for cucumber plant results on PMK soil. Biosaka treatment was the best treatment in this research. There was no interaction between Biosaka and NPK fertilizer on all observed variables.